Negative Impact of the Hedonism Lifestyle in the Student Environment - Deftarani Deftarani; Faiq Dhiyaulhaq; Rafli Nurochman (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
A hedonistic lifestyle appears among students, where this hedonistic lifestyle holds the view that pleasure is the main goal of life, causing students to buy various types of goods or items that they do not really need but only to fulfill their personal desire for pleasure. This research aims to answer questions about what is meant by hedonism, why many students live a hedonistic lifestyle and what its impacts are and how to prevent the emergence of these hedonistic traits. The method in this research uses a qualitative method which uses observation method data from YouTube and 2 articles. The results of this research found that the causes of a person's hedonic behavior are internal and external factors, and the environment in these internal factors is influenced by dissatisfaction with what he has and external factors are caused by open access to information. Or globalization so that the habits of outsiders who tend to be hedonistic are often imitated by students. Environmental factors are influenced by pressure from friendships which causes students to need validation from other people. These factors have a negative impact, such as: Consumerism, selfishness, changes in students' attitudes and way of thinking from academic to apathetic, tending to prioritize worldly things and not considering the negative impact on lecture activities. This research contributes to educating students about preventing hedonic lifestyles among students.